Investigating the relationship between symbols in the physical environment of the elderly and creating a sense of vitality in them - Farahnaz Tahiri; Hamzeh Gholamalizadeh (مهندسی و مدیریت ساخت)
Considering the increasing trend of the elderly population and its impact on the society, improving their quality of life is one of the most important issues of the current century. Therefore, knowing the environmental factors that can be effective in improving their living conditions; It is necessary. The purpose of this research is to understand the needs of the elderly and provide solutions to create a sense of vitality in them. The research method in this research is descriptive-analytical and the method of analysis is done through logical reasoning. In this article, first, the basic needs of the elderly are examined, and then, by comparing and evaluating the research findings, solutions are presented to design and optimize their living environment. The findings of this research showed that attention to their psychological needs is one of the issues that can make the elderly adapt to their care centers. To some extent, the built environment can be a platform or facilitator to meet some of these needs. The elderly do not tend to make major changes in the environment that surrounds them. Establishing the mental connection of the elderly with the perceptible meanings of the physical environment, or in other words matching the perceptual findings from the environment with "mental schemas" from their past experiences; It can have the most impact on other needs. Therefore, to create a connection between the built environment today and the past, it seems that referring to the past and reviewing memories by using symbols and signs in the built environment can be effective in creating a sense of vitality for the elderly.